Trainee perspective of the causes of stress and burnout in surgical training: a qualitative study from Wales - Luke Hopkins; Oliver Luton; Richard J Egan; Wyn G Lewis; David Bryan Thomas Robinson; Osian Penri James; Arfon GMT Powell; Sarah Hemington-Gorse; Katie Mellor; Rhiannon L Harries (BMJ Open)
Objectives Stress and burn-out among surgical trainees has been reported most prevalent in core surgical trainees (CST) and female trainees in particular. This study aimed to identify factors perceived by CSTs to be associated with stress and burnout in those at risk.Design An open-ended questionnaire was distributed to 79 CSTs and two researchers categorised responses independently, according to Michie’s model of workplace stress.Setting A UK regional postgraduate medical region (Wales).Participants Sixty-three responses were received; 42 males, 21 females. The response rate was 79.7%.Results Inter-rater reliability was good (k=0.792 (79.2%), p<0.001). The most common theme of Michie’s model related to CST stress and burnout was career development, with most statements associated with curriculum, examination and academic demands required to attain a CST certificate of completion of training, and higher surgical national training number appointment. This was closely followed by those intrinsic to the job with recurrent discussion around the difficulties balancing work perceived to be service provision (ward work and on-calls), outpatient clinic and operative experience. Conversely, the most common themes relevant to stress and burnout among female trainees were associated with relationships at work (primarily the male-dominated nature of surgery), extraorganisational factors (family–work life balance) and individual characteristics (personality and physiological differences).Conclusion CSTs’ perceptions regarding the causes of National Health Service related stress and burnout are numerous, and these findings provide a basis for the development of targeted stressor counter-measures to improve training and well-being.